2019
DOI: 10.1038/s41431-018-0326-9
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 10q24 locus: broadening the clinical and radiological spectrum

Abstract: Split-hand-split-foot malformation (SHFM) is a rare condition that occurs in 1 in 8500-25,000 newborns and accounts for 15% of all limb reduction defects. SHFM is heterogeneous and can be isolated, associated with other malformations, or syndromic. The mode of inheritance is mostly autosomal dominant with incomplete penetrance, but can be X-linked or autosomal recessive. Seven loci are currently known: SHFM1 at 7q21.2q22.1 (DLX5 gene), SHFM2 at Xq26, SHFM3 at 10q24q25, SHFM4 at 3q27 (TP63 gene), SHFM5 at 2q31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…The variant overlaps with the most common duplications associated with ectrodactyly (de Mollerat et al 2003 ; Klopocki et al 2012 ). The minimal overlapping region of pathogenic SHFM3 duplications includes BTRC , POLL, and DPCD (Holder-Espinasse et al 2019 ). The inversion described here is copy number neutral, suggesting that positional effects rather than gene dosage might be responsible for the phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant overlaps with the most common duplications associated with ectrodactyly (de Mollerat et al 2003 ; Klopocki et al 2012 ). The minimal overlapping region of pathogenic SHFM3 duplications includes BTRC , POLL, and DPCD (Holder-Espinasse et al 2019 ). The inversion described here is copy number neutral, suggesting that positional effects rather than gene dosage might be responsible for the phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The inversion described here is copy number neutral, suggesting that positional effects rather than gene dosage might be responsible for the phenotype. It includes a topologically associating domain boundary (Holder-Espinasse et al 2019 ) and is likely to change the enhancer landscape at the SHFM3 locus leading to FGF8 misregulation causing ectrodactyly.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The duplications at the 10q24.32 locus associated with this condition overlap almost completely (except FGF8) with duplications implicated with split hand/foot malformation (SHFM3), a common limb defect. 3,11,[43][44][45] Despite their similar sizes, the duplications result in very different phenotypes: while SHFM3 affects mainly hands and feet, the slightly larger duplications reported here cause femoral A B Figure 4. Genome architecture at the region of duplication and tissue-specific Fgf8 expression in WT and Fgf8 þ/dup mice embryos (A) cHi-C maps of WT and Fgf8 þ/dup E11.5 hindlimb buds.…”
Section: Discussionmentioning
confidence: 85%
“…Comparative analysis revealed that the femoral hypoplasia duplications reported here almost completely overlap with 10q24.32 duplications that are known to associate with split hand/foot malformation (SHFM3 [MIM: 246560]), an entirely different limb malformation. 11 The only unique gene to the femoral hypoplasia duplications was FGF8, a key regulator of limb development that is known to direct proximo-distal growth [36][37][38] (Figure 1C). While initially gene dosage effects of FGF8 seemed like a promising explanation for the femoral hypoplasia phenotype, we also identified several healthy individuals without skeletal abnormalities carrying smaller duplications that include FGF8 in control cohorts [12][13][14][15][16] (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Although all the 17 likely pathogenic (LP) CNVs were not found in healthy individuals or in DGV ( http://dgv.tcag.ca/dgv/app/home ). They have been identified in more than one ID patients before ( Mégarbané et al, 2000 ; Rauch et al, 2003 ; Roggenbuck et al, 2004 ; Hellani et al, 2010 ; Dimitrov et al, 2011 ; Melis et al, 2012 ; Rush et al, 2013 ; Castillo et al, 2014 ; Balasubramanian et al, 2016 ; Leffler et al, 2016 ; Zhou et al, 2016 ; Akcakaya et al, 2017 ; Bonati et al, 2019 ; Holder-Espinasse et al, 2019 ; Allach El Khattabi et al, 2020 ). To determine the inheritance pattern, the parental DNA was available from the parent in 21 cases.…”
Section: Resultsmentioning
confidence: 99%